Integrated Research for Integrated Ocean Management - Rölfer, Lena; Liconti, Arianna; Prinz, Natalie; Klöcker, Clara Antonia (Frontiers in Marine Science, 2021)
With the start of the United Nations (UN) Decade of Ocean Science for Sustainable Development in 2021, research priorities to support the sustainable use of coastal and ocean resources and their conservation are in the spotlight. However, to date comprehensive regulation and management of multifaceted and multi-used ecosystems has proven challenging. This is partly due to the complexity of coastal and ocean social-ecological systems (SES), as well as the multitude of approaches to manage those spaces. In order to address such challenges, magnified by often-conflicting interests between economic activities and nature conservation, there is an urgent need for integrated approaches that bridge the gap between science, policy and society, as well as across different epistemological boundaries set by various management approaches. Consequently, the interest in multi-, inter-, and transdisciplinary research approaches at the national and international levels has been growing. In light of the recently started Decade of Ocean Science, this paper aims at providing key considerations for research approaches that tackle the outlined challenges in managing the ocean space. From a survey targeted at projects and initiatives that apply multi-, inter-, and transdisciplinary approaches, we draw examples of challenges and good-practices. Based on this, we propose three key considerations for an integrated research approach, including (1) target setting, resource management, and adaptive planning; (2) knowledge production and responsiveness toward policy and society; and (3) co-design, co-development, cooperation, as well as effective communication. The considerations laid out in this paper are aimed at the effective translation between science, policy, and society in support of sustainable coastal and ocean governance within the Decade of Ocean Science.